Assessment of water quality in the downstream of the Amu Darya basin - Karimboev Feruzbek; Gulomov Daulet; Tillayeva Zarina (E3S Web of Conferences, 2021)
Ecosystem vulnerability increases significantly when anthropogenic factors overlap with the effects of adverse climate change, which together negatively affect biodiversity and ecosystem functioning. According to ADB forecasts, the inflow to the lower reaches of the Amu Darya will decrease by 26-35% by 2050. The combined effect of higher water demand and lower inflow will increase the current water shortage - the annual water shortage will increase to 50% of the total demand. In connection with the projected changes, the current state of water resources of the Amu Darya river, as well as the need for the socioeconomic development of the region, the task of assessing the projected impact of climate change on the availability and quality of water resources becomes urgent.